Exposure to improved nutrition from conception to age 2 years and adult cardiometabolic disease risk: a modelling study - Nicole D Ford, PhD; Jere R Behrman, PhD; John F Hoddinott, DPhil; John A Maluccio, PhD; Reynaldo Martorell, PhD; Manuel Ramirez-Zea, PhD; Aryeh D Stein, PhD (Elsevier, 2018)
Summary: Background: Low-income and middle-income countries with populations that are chronically undernourished in early life are undergoing a nutrition transition and are experiencing an epidemic of cardiometabolic disease. These dual burdens are thought to be causally related; therefore, the extent to which improvements in early-life nutrition can offset adult-onset disease is important. The aim of this study was to examine whether improvement of protein-energy nutrition from conception to age 2 years can attenuate the risk of cardiometabolic disease. Methods: We followed up a cohort of 2392 individuals born between Jan 1, 1962, and Feb 28, 1977, in four villages in Guatemala who had participated in a cluster-randomised protein-energy nutritional supplementation (Atole) trial. Of 1661 participants available for follow-up from Feb 26, 2015, to April 29, 2017, we studied 684 women and 455 men. We assessed cardiometabolic disease risk at ages 37-54 years using anthropometry, fasting and post-challenge glucose, fasting lipid concentrations, and blood pressure. We used generalised linear and logistic regression modelling to estimate the effect of Atole from conception to age 2 years (the first 1000 days) on cardiometabolic disease risk. Findings: Exposure to Atole from conception to age 2 years was associated with increased fatness (body-mass index [1·29 kg/m2, 95% CI 0·08 to 2·50], body fat [1·73%, 0·20 to 3·26], and obesity [odds ratio 1·94, 1·11 to 3·40]), diastolic blood pressure (1·59 mm Hg, −0·74 to 3·92), and blood lipids (total cholesterol [10·10 mg/dL, 0·80 to 19·40] and non-HDL cholesterol [10·41 mg/dL, 1·51 to 19·31]), reduced post-challenge glucose (-5·84 mg/dL, −12·51 to 0·83), and reduced odds of diabetes (odds ratio 0·46, 0·21 to 0·97). We found stratum heterogeneity by sex in pooled models for non-HDL cholesterol (4·34 mg/dL, 95% CI −6·86 to 15·55 for women vs 19·84 mg/dL, 5·86 to 33·82 for men) and post-challenge glucose (-0·19 mg/dL, −8·63 to 8·24 for women vs −13·10 mg/dL, −23·64 to −2·56 for men). p values for interaction of sex and exposure to Atole from conception to age 2 years were 0·09 and 0·04, respectively. Interpretation: Improved protein-energy nutrition from conception to the 2nd birthday reduced the odds of diabetes at ages 37-54 years; however, this protein-energy supplementation also increased the risk of obesity and several obesity-related conditions. Our findings suggest a mixed ability of protein-energy nutritional supplementation in early life to prevent adult cardiometabolic disease incidence in the context of high childhood stunting and high adult overweight and obesity. Funding: National Institutes of Health.